2022
DOI: 10.25073/2588-1159/vnuer.4677
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Knowledge of Green Chemistry in Senior Secondary Schools in Kwara State, Nigeria

Abstract: There have been series of advocacies all over the world to prepare future scientists who would take up the challenge of eradicating environmental pollution through the deployment of scientific knowledge such as green chemistry. This study investigated teachers’ knowledge of green chemistry in Kwara State, Nigeria. The Green Chemistry Knowledge Questionnaire (GCKQ) was used to collect the data. Answers were provided to the research questions using the mean and percentage, while the research hypotheses were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Mostly, teachers are aware of the peer to peer technique, collaborative technique, concept mapping learning approach, and the think-pair strategies among others. In support of the above findings, Oyelekan, et al (2017) also found that Computer Assisted Instruction (CAI), project method, and blended learning among others were the innovative teaching strategies that are very much knowledgeable to the teachers and the extent of their use depends on this awareness of these innovative teaching strategies…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Mostly, teachers are aware of the peer to peer technique, collaborative technique, concept mapping learning approach, and the think-pair strategies among others. In support of the above findings, Oyelekan, et al (2017) also found that Computer Assisted Instruction (CAI), project method, and blended learning among others were the innovative teaching strategies that are very much knowledgeable to the teachers and the extent of their use depends on this awareness of these innovative teaching strategies…”
Section: Resultsmentioning
confidence: 66%
“…They refer to approaches to teaching and learning that puts learners first and foremost and thrive to bring learning to the doorstep of the learners (Nwuba et al, 2022). The innovative teaching strategies encompass a wide array of approaches, such as project-based learning, inquiry, RQA, flipped classrooms, problem-based learning, gamification, and the integration of digital tools and simulations (Alahmari et al, 2023, Choirunisa' et al, 2024Damopolii, Nunaki, et al, 2019;Oyelekan et al, 2017;Santos et al, 2023). Teaching strategies can take various forms, including traditional didactic instruction, collaborative learning, inquiry-based learning, and technology-enhanced instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Chemistry holds significant importance in the realm of science because it is closely interconnected with various other branches of scientific inquiry. In addition, chemistry also has extensive and influential relationships in everyday life [4]. At school, chemistry is a subject that has characteristics in the form of interrelated concepts.…”
Section: Introductionmentioning
confidence: 99%